Road Tunnel Axial Fan Performance In Situ Test: Taking Qinling Zhongnan Mountain Highway Tunnel as an Example. (4th April 2019) - Wang, Yongdong; Han, Xingbo; Zhou, Tianyue; He, Zhiwei; Tian, Feilong; Zheng, Zhuoqi; Zhao, Haiping
Abstract : Axial fans play a pivotal role in the road tunnel ventilation system. Qualified performance of the axial fan is important for both safety and air quality maintenance reasons. Axial fans performance in situ test of Qinling Zhongnan Mountain highway tunnel, the second longest road tunnel in the world, is presented in this research. Performance test items and the qualification criterion, as well as a general framework for the road tunnel axial fan assessment, are recommended. Log-Tchebycheff method is suggested to confirm the location for the measuring lines and points. The precision of the log-Tchebycheff method in air flow rate measuring is verified by comparing with the biharmonic spline interpolation fitting result. The research shows that the log-Tchebycheff method has high precision and good efficiency in the air flow rate measurement of the road tunnel air duct. What is more, the biharmonic spline interpolation fitting method can be applied to obtain a more accurate result. The number of interpolation points of the biharmonic spline interpolation fitting method should be bigger than 2000 to provide quality results.